2016
DOI: 10.1016/j.poly.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Amidoximes as ligand functionalities for braided polymeric materials for the recovery of uranium from seawater

Abstract: The formation constants of the UO 2 2+ cation with the amidoximate ligands bzam (benzamidoxime) and acetam (acetamidoxime) are reported. These are of interest in light of their proposed use as the functional groups of extractants for uranium in seawater. The formation constants of bzam with UO 2 2+ were measured by monitoring the absorbance of the π→π* transitions in the UV spectrum of the bzam ligand in the presence of 1:1 UO 2 2+ as a function of pH. This yielded log K 1 = 12.4 for UO 2 2+ with bzam, and log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…A variety of adsorbents have been evaluated, hydrous titanium oxide, as one of the most widely described inorganic material (Yamashita et al, 1980b;, was found that carbonate ion from the uranyl tricarbonate complex (UO 2 (CO 3 ) 3 4− ) was released into the solution during the adsorption process (Yamashita et al, 1980a). Recently, synthetic polymers with amidoxime functional groups had been mainly used because of their high affinity in chelating U(VI) in seawater (Zhang et al, 2003;Das et al, 2009;Kim et al, 2014;Lashley et al, 2016). The uranium adsorption proceeded by ligand exchange of three carbonate ions on the central uranyl ion with two amidoxime groups, accompanied by deprotonations (Hirotsu et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of adsorbents have been evaluated, hydrous titanium oxide, as one of the most widely described inorganic material (Yamashita et al, 1980b;, was found that carbonate ion from the uranyl tricarbonate complex (UO 2 (CO 3 ) 3 4− ) was released into the solution during the adsorption process (Yamashita et al, 1980a). Recently, synthetic polymers with amidoxime functional groups had been mainly used because of their high affinity in chelating U(VI) in seawater (Zhang et al, 2003;Das et al, 2009;Kim et al, 2014;Lashley et al, 2016). The uranium adsorption proceeded by ligand exchange of three carbonate ions on the central uranyl ion with two amidoxime groups, accompanied by deprotonations (Hirotsu et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that amidoximation 21,77,[108][109][110][111][112][113][114][115][116] 33-43 of PAN led to uranyl uptake that was dependent on pH, and additional gains in U extraction efficiency were achieved using high surface area to volume nanomaterials 117,118 and electrospun fibers. 21,119,120 Here, high , and spectra are similar to previous literature reports.…”
Section: A31 Characterization Of and Uranyl Uptake On Pan And Ao-pamentioning
confidence: 99%
“…Finally, intensities and Γ increase but vibrational frequencies remain constant when the solution pH used during uptake increases from 4 to 6.8. Because pH impacts both uranyl speciation 92 and AO-PAN functional group protonation 113,124 both would influence the resulting vibrational features.…”
Section: A32 Evaluation Of Uranyl Uptake On Ao-pan Mats Using Normamentioning
confidence: 99%
See 2 more Smart Citations